Investment in human capital through upper-secondary and tertiary education - Blöndal, Sveinbjörn (OECD Publishing, 2003)
This article examines various efficiency and equity aspects related to the skill acquisition of young people and older adults. The analysis suggests that human capital investment is associated with significant labour-market gains for individuals, including higher post-tax earnings and better employment prospects, which exceed the investment costs, mainly foregone earnings and tuition fees, by a significant margin. It also shows that the net benefits are strongly influenced by policy related factors, such as study length, tuition subsidies and student support. Overall, the estimates reported in the article indicate that there are strong incentives for the average student to continue studying beyond the compulsory schooling age, and also point to the benefits of such investment in education for society as a whole. However, the net gains fall with age, mainly reflecting a shorter period to take advantage of the benefits that come with education. Finally, the article notes that students in higher education tend to come from more affluent backgrounds and that they benefit from large public subsidies, whereas young people from disadvantaged backgrounds are less likely to participate in tertiary education and thus benefit from public subsidies